2007
DOI: 10.1063/1.2425013
|View full text |Cite
|
Sign up to set email alerts
|

Intense visible photoluminescence in Ba(Zr0.25Ti0.75)O3 thin films

Abstract: Photoluminescence at room temperature in Ba(Zr0.25Ti0.75)O3 thin films was explained by the degree of structural order-disorder. Ultraviolet-visible absorption spectroscopy, photoluminescence, and first principles quantum mechanical measurements were performed. The film annealed at 400°C for 4h presents intense visible photoluminescence behavior at room temperature. The increase of temperature and annealing time creates [ZrO6]–[TiO6] clusters in the lattice leading to the trapping of electrons and holes. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 17 publications
0
33
0
1
Order By: Relevance
“…Our purpose with the BaZrO 3 -od model is to provide a simple scheme to help in the comprehension of PL emission mechanisms linked to the structural defects of the electronic structure without to suppress completely the geometry of the cell. Using the same distorted model, we have successfully explained the PL emission of several titanates [38][39][40] and zirconates titanates [41][42][43]. The model suggests that the increase of heat treatment temperature reduces the disorder in BaZrO 3 lattice, creating electron-captured oxygen vacancies.…”
Section: Bazro 3 Structure and Modelsmentioning
confidence: 80%
“…Our purpose with the BaZrO 3 -od model is to provide a simple scheme to help in the comprehension of PL emission mechanisms linked to the structural defects of the electronic structure without to suppress completely the geometry of the cell. Using the same distorted model, we have successfully explained the PL emission of several titanates [38][39][40] and zirconates titanates [41][42][43]. The model suggests that the increase of heat treatment temperature reduces the disorder in BaZrO 3 lattice, creating electron-captured oxygen vacancies.…”
Section: Bazro 3 Structure and Modelsmentioning
confidence: 80%
“…14,15 The PL at room temperature occurs due to structural disorder of the system. Therefore, if the system is totally disordered, then the PL does not exist; moreover, a totally ordered system does not exhibit PL.…”
Section: Resultsmentioning
confidence: 99%
“…In the calculus, the XANES spectrum of BaTiO 3 phase was adopted as [37,69,70]. On the other hand, mechanical calculations based on the density functional theory (DFT) [71] showed that all four phases (cubic, tetragonal, orthorhombic and rhombohedral) of BaTiO 3 6 ].…”
Section: Fourier Transform Infrared Spectroscopy Analysesmentioning
confidence: 99%